2014
DOI: 10.1186/1475-2875-13-449
|View full text |Cite
|
Sign up to set email alerts
|

Does socio-economic status explain the differentials in malaria parasite prevalence? Evidence from The Gambia

Abstract: BackgroundMalaria is commonly associated with poverty. Macro-level estimates show strong links between malaria and poverty, and increasing evidence suggests that the causal link between malaria and poverty runs in both directions. However, micro-level (household and population) analyses on the linkages between malaria and poverty have often produced mixed results.MethodsThe Gambia Malaria Indicator Survey (MIS) 2010/11 was carried out between November 2010 and January 2011. Laboratory-confirmed malaria and wea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
35
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 34 publications
8
35
0
Order By: Relevance
“…In a community level study in Malawi, children under 5 years and those between 5 and 19 years were reported to benefit equally from community bed net coverage [37]. We found another study in the Gambia that reported similar findings to our study [38]. It is possible that children <5 years were less affected than the 5-18 age group because the children are given priority by their guardians to sleep under LLINs, compared with older children.…”
Section: Discussionsupporting
confidence: 80%
“…In a community level study in Malawi, children under 5 years and those between 5 and 19 years were reported to benefit equally from community bed net coverage [37]. We found another study in the Gambia that reported similar findings to our study [38]. It is possible that children <5 years were less affected than the 5-18 age group because the children are given priority by their guardians to sleep under LLINs, compared with older children.…”
Section: Discussionsupporting
confidence: 80%
“…Temporal trends show declining malaria transmission in The Gambia and Coastal Kenya 17, 33, 34, 40 , although not in Western Kenya 41 . Asymptomatic parasite prevalence is lowest in The Gambia at 8.7% 42 , intermediate in Kilifi at 14% 43 and slightly higher in Rachuonyo South at 16% 44 .…”
Section: Methodsmentioning
confidence: 86%
“…This type of house don’t offer much protection against the elements or vectors of disease unless are raised above ground [ 29 ], or its occupants use a mosquito net, but allows air flow for comfort. For example, a recent survey at the household level in The Gambia showed that children from the poorest quintiles living in houses build with poor walls, roofs and windows construction materials, were associated with a high prevalence of malaria [ 15 ], though, in the general population only poor wall housing materials were associated with a high prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…Malaria has been correlated with low socio-economic development and poverty [ 10 ], and recent evidence suggests, that a causal pathway between poverty and malaria runs in both directions [ 15 ]. Furthermore, it has been pointed out that low socio-economic status (SES) doubles the risk of clinical malaria, reducing the capacity of countries to enter the elimination phase and that type of house construction is associated with increasing risk of malaria infection [ 16 - 20 ].…”
Section: Introductionmentioning
confidence: 99%